Hypoxia - P. F. Litvitsky (Вопросы современной педиатрии)
The discourse characterizes types, causes and key links of the pathogenesis of different types of hypoxia, their main manifestations and mechanisms of their development, disorders in the body under hypoxic conditions, principles of their elimination. The mechanisms of a body adaptation to acute and chronic hypoxia, as well as the idea of its superoxygenation are described.